PEMANFAATAN LIMBAH TAMBANG UNTUK BAHAN KONSTRUKSI BANGUNAN - Hendra Riogilang (EKOTON, 2013)
Infrastructure development and housing is an industry which requires big enough cost, construction/building materials, and energy. Saving on these three components in industrial business to be as a main target in almost all developing countries. To reach the target, there are intensive efforts should be done to effectively utilize that of mining waste disposal or tailing.Tailing always becoming a serious problem which commonly to be considered as a main cause of environmental damage, but in fact also be utilized to good advantage. In order not generate a negative impact hence it needs a better management by reutilizing it properly and wisely in optimum condition. One of the efforts which can be done is by increasing its usefulness as construction/building materials. Utilization of the tailing to be as construction/building materials constituting a solution for energy saving, preservation of environment, and conservation of mineral resources